Is Modernity Single and Universal?: Olaju and the Multilateral Modernity - Adeshina Afolayan (Yoruba Studies Review, 2021)
This essay confronts two orthodoxies at the heart of the modernity debate. The first is that modernity, which supposedly originated from the West, is a single and universal historical development. The assumption therefore is that any genuine modernity elsewhere must proceed from aping the structuratlon of western modernity. The second orthodoxy challenges the first, and coalesces around the idea of multiple modernities, which do not share the historical contours of western modernity. Yet, these modernities supposedly take their initiatives from the original source in the West. On the contrary, I will argue that these orthodoxies ignore a critical fact of global history: The concept of the modern was shaped and reshaped within a multilateral framework of confrontations and conflicts amongst cultures and societies, which enabled each society to creatively respond and adapt itself to the changes it confronted. I will use the Yoruba concept of olaju as a conceptual foil to reconfigure the understanding of this multilateral modernity. With olaju, we arrive at the conclusion that both Europe and non-Europe are complicit in the formation and configuration of what it means to be modern. It is only from this premise that the foundation of multiple modernities can properly be erected. It is also from this premise that various societies can take charge of the elements of social change as well as the power and knowledge dynamics involved in it.